ANALYSIS OF VARIABLES INFLUENCING CONSUMER PURCHASE INTENTION ON TOKOPEDIA - Dwilestari, Charisma; Erdiansyah, Rezi (Graduate Program of Universitas Tarumanagara, 2023)
With the progression of time and technology, society is increasingly abandoning traditional methods and shifting towards online transactions. This change brings consequences in how products are promoted and how consumers are convinced to make purchases. Therefore, this research aims to identify potential variables that may influence consumer purchase intention on the Tokopedia e-commerce platform. The variables under investigation include e-WOM (electronic Word-of-Mouth), online reviews, brand familiarity, and trustworthiness. The analysis method employed is Partial Least Squares (PLS). Research data was obtained through a survey involving over 300 active Tokopedia users. The analysis results demonstrate that brand familiarity, e-WOM, and online reviews have a positive and significant impact on consumer purchase intention. Additionally, it was found that trustworthiness acts as a mediator between brand familiarity, e-WOM, online reviews, and consumer purchase intention. This study provides a significant contribution to the understanding of factors influencing consumer purchase intention on the e-commerce platform, specifically Tokopedia. These findings can serve as a basis for developing more effective marketing strategies to enhance consumer purchase intention and trust in Tokopedia as an e-commerce platform. The practical implications of this research emphasize the importance of considering brand familiarity, e-WOM, online reviews, and trustworthiness in efforts to increase consumer purchase intention on Tokopedia.